Tren Riset Kebijakan Pendidikan Inklusif di Asia: Analisis Bibliometrik 2005-2025 - Afnan Iliya Tsabita; Winda Dewi Listyasari; Teguh Trianung; Syafaat Ariful Huda (Media Manajemen Pendidikan, 2026)
This study aims to analyze research trends in inclusive education policy in the Asian region during the period 2005–2025. A bibliometric approach was employed using the PRISMA method to select articles from the Scopus database through Publish or Perish, complemented by manual searches on Google Scholar. From an initial 184 documents, 21 articles met the inclusion criteria. Descriptive and visual analyses were conducted using VOSviewer, with a minimum threshold of three keyword occurrences. The results indicate a significant increase in publications after 2015, peaking during the 2023–2025 period. The most productive countries include China, Indonesia, Malaysia, and Thailand. Keyword mapping revealed two main clusters: policy and legal frameworks, and implementation and educational equity. These findings highlight a persistent gap between regulation and practice in inclusive education across Asia. This study contributes to a comprehensive mapping of inclusive education policy research trends and provides an empirical foundation for strengthening policy and implementation at the regional level.